IMPACT OF THE INFLAMMATORY AND ISCHEMIC HEART DISEASE MARKERS INTO THE OVERALL CARDIOVASCULAR MORTALITY IN SENILE CITIZENS OF A LARGE CITY (THE DATA FROM SAHR TRIAL) - S. A. Shalnova; S. E. Evstifeeva; A. D. Deev; V. A. Metelskaya; A. V. Kapustina; G. A. Muromtseva; Yu. A. Balanova; E. M. Tuaeva; A. E. Imajeva; N. V. Kiseleva; M. A. Shkolnikova (Российский кардиологический журнал, 2015)
Aim. To study the associations of inflammation markers (hsCRP, IL-6, FG, leucocytes, ESR) with coronary heart disease (CHD) and their impact on overall cardiovascular mortality in old citizens of Moscow. Material and methods. We used the data from prospective cohort study “Stress, Ageing and Health in Russia” (SAHR) — a representative selection from non-organized inhabitants of Moscow citizens from 55 years old. The duration of the study has been 5 years (since June 2006 to May 2011) at FSBI SSICPM of the Healthcare ministry and included 1871 persons. All participants underwent standard questioning. Into analysis we included gender, age, educational level, classic risk factors. For the assessment of current subclinical inflammation we used high-sensititvity C-reactive protein (hsCRP), interleucine 6 (IL-6), fibrinogen (FG), leucocytes, erythrocyte sedimentation rate (ESR). For CHD screening, we used standard ROse questionnaire and ECG pattern by Minnesota coding. Mortality was evaluated under the continuous death cases registry. At the beginning of 2014 totally 314 fatal cases registered, including 186 of CVD. Results. There were significant associations more prominent in women, of the smoking in anamnesis, increased BP levels, obesity and CHD, diagnosed at a strict multifactorial analysis. Among inflammation markers, the significant correlation with CHD showed hsCRP and IL-6. In monofactor analysis, correct just for the age and gender, all studied markers significantly associated with total and cardiovascular mortality. In multidimensional model of proportional risk, that included gender, age, CHD by strict or mild criteria, all risk factors and al inflammation markers, remained statistically significant by their impact on mortality from all causes and from CVD, except gender, age and strict-criteria CHD (HR — 95% CI: 1,5-1,15;1,96, р=0,0029 and 2,0-1,41;2,88, р=0,0001, resp.), smoking, hsCRP (HR — 95% CI: 1,031,01;1,05, р=0,0002 and 1,03-1,01;1,05, р=0,007, resp.) and IL-6 (HR — 95% CI: 1,02-1,0;1,03, р=0,04 и 1,02-1,0;1,04, р=0,022, resp.). Conclusion. HsCRP, IL-6 and CHD by strict criteria, even after correction on gender, age and traditional risk factors, significantly correlate with total and cardiovascular mortality in men and women of 55 y.o. and older.